Drop-Out and Transfer-Out Intentions: The Role of Socio-Cognitive Factors - Nemtcan, Efim; Sæle, Rannveig Grøm; Gamst-Klaussen, Thor; Svartdal, Frode (Frontiers in Education, 2020)
Academic attrition is a worldwide problem representing a significant economic loss and a disadvantage for students in terms of health and career prospects. We focus on the roles of academic skills, academic self-efficacy, and students’ integration in exploring their relation to attrition intentions. Based on existing research, we expected a negative relation between academic skills and attrition intentions, with academic self-efficacy and students’ integration as possible mediators. Furthermore, it was expected that this relationship would be dependent on the outcome variable being measured (i.e., drop-out, transfer university, and transfer study field intentions). These hypotheses were investigated among Norwegian university students in a questionnaire study (total N = 756). Results supported, as predicted, the mediatory roles of academic self-efficacy and students’ integration. Importantly, significant variability was indicated in comparison of the different outcome measures, with academic self-efficacy having a larger mediation effect in case of drop-out and transfer study field intentions. We conclude that academic self-efficacy is important in understanding the relationship between students’ academic skills and attrition intentions. Our results provide an evidence that might facilitate development of assistance programs aiming to reduce academic attrition.